Becoming Indians: Cervantes and García Lorca - Subhas Yadav (Universitat Autònoma de Barcelona, 2019)
This article deals with the reception of Cervantes’s works, particularly Don Quixote de la Mancha in India, and the select works of Andalusian poet Federico García Lorca.